Case Report: Clinical complete response of advanced renal cell carcinoma associated with Xp11.2 translocation/TFE3 gene fusion by treated by camrelizumab and axitinib: A rare case report - Zhao, Juping; Dai, Kun; Xie, Jialing; Fang, Chen; Chen, Na; Dai, Jun; Xu, Danfeng (Frontiers in Pharmacology, 2022)
Renal cell carcinoma (RCC) associated with Xp11.2 translocation/TFE3 gene fusions is a rare subtype of renal tumor. This entity predominantly occurs in juveniles, but rarely in adults. Xp11.2 translocation RCC (tRCC) Patients with lymph node or organ metastasis are associated with poor prognosis, and strategy remains controversial. Herein, we presented our experience of the diagnosis and treatment for an adult case of Xp11.2 tRCC. In our clinical practice, a 32-year-old male manifested fever and right flank paroxysmal blunt pain, and computed tomography showed an inhomogeneous mass, 6 cm in diameter, in the right kidney. Then right partial nephrectomy (PN) and renal hilar lymph node dissection by laparoscopic surgery was performed. Pathology revealed that the tumor cells were positive for TFE3 immunohistologically and positive TFE3 break-apart fluorescence in situ hybridization assay. A splice site mutation c.1544-1G>T of protein tyrosine phosphatase receptor delta (PTPRD) was detected by next-generation sequencing and weak PTPRD expression was confirmed in tumor tissues compared to tumor periphery. This patient was diagnosed as stage III RCC, and received immune checkpoint inhibitor (camrelizumab) in combination with tyrosine kinase inhibitor (axitinib) treatment for one year. He achieved clinical complete response with no sign of recurrence or metastasis. PTPRD mutation might be a favorable indicator for Xp11.2 tRCC patients managed by PN and followed by the adjuvant therapy of immune checkpoint inhibitor and tyrosine kinase inhibitor.